2014
DOI: 10.3346/jkms.2014.29.11.1562
|View full text |Cite
|
Sign up to set email alerts
|

Kind and Estimated Stocking Amount of Antidotes for Initial Treatment for Acute Poisoning at Emergency Medical Centers in Korea

Abstract: Antidotes for toxicological emergencies can be life-saving. However, there is no nationwide estimation of the antidotes stocking amount in Korea. This study tried to estimate the quantities of stocking antidotes at emergency department (ED). An expert panel of clinical toxicologists made a list of 18 emergency antidotes. The quantity was estimated by comparing the antidote utilization frequency in a multicenter epidemiological study and the nation-wide EDs' data of National Emergency Department Information Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Although adequate measures are available in most developed countries to combat poisoning when reported early, more efficient methods of dissemination and administration of these antidotes are also under appraised. Studies, however, revealed inadequate stocking [5,6,[20][21][22] and in some cases, absence of some essential antidotes [4] as major hindrances. This is in sharp contrast to the experience in most rural areas and developing countries where antidotes are hardly available, leaving them with the only option of herbal antidotes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although adequate measures are available in most developed countries to combat poisoning when reported early, more efficient methods of dissemination and administration of these antidotes are also under appraised. Studies, however, revealed inadequate stocking [5,6,[20][21][22] and in some cases, absence of some essential antidotes [4] as major hindrances. This is in sharp contrast to the experience in most rural areas and developing countries where antidotes are hardly available, leaving them with the only option of herbal antidotes.…”
Section: Discussionmentioning
confidence: 99%
“…There are no general classifications of antidotes as different authors have used different classifications. For instance, antidotes have been classified based on their documented efficacy [5], mechanisms of action [29,30], the group of poisons they are used against [31] and based on clinical urgency of use [12].…”
Section: Classes Of Antidotes and Mechanism(s) Of Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, recent evidence indicates persistent deficiencies in antidote stocking worldwide. 3,4,14,15 The causes of this serious problem are unknown, but are likely related in part to limited education, inadequate awareness, infrequent use, interruptions in supply, and limited hospital pharmacy resources. Previous studies have found that larger hospitals are more likely to have adequate stocks of antidotes than smaller or rural hospitals.…”
Section: Introductionmentioning
confidence: 99%